Assessment of Knowledge on Sexual Assault Forensic Examination among Nurses in India: A Cross-Sectional Study - Renjulal Yesodharan; Tessy Treesa Jose; Vinod C. Nayak (Indian Journal of Forensic Medicine and Pathology, 2026)
Background: Sexual violence is a major global public health and human rights issue that affects women and children in various societies. Survivors of sexual assault need immediate medical care and forensic examination, where healthcare professionals play a very crucial role. Nurses are the first point of contact in most of the health care settings to give immediate and prompt care. Nurses help to identify injuries, collect, preserve, and pack evidence, document findings and maintain chain of custody. However, limited training in forensic aspects may impact their ability to perform this task effectively. Objectives: This study aimed to evaluate the knowledge level regarding sexual assault examination among registered nurses and final-year nursing students Methods: A quantitative cross-sectional study was conducted with 276 participants from hospitals and nursing colleges in Dakshina Kannada and Udupi districts. Data were collected using socio-demographic proforma and a 38 item knowledge questionnaire on sexual assault nurse examination (KQSANE). Descriptive statistics summarize knowledge levels. Spearman’s correlation and generalized linear model regression were used to explore the relationships between knowledge domains and socio-demographic variables. Results: The findings indicate that overall knowledge about sexual assault examination was inadequate, with most participants demonstrating poor knowledge. Among the knowledge areas, legal and ethical knowledge domain received the highest scores. The domain forensic examination and imaging received the lowest scores. Significant positive correlation was found between the overall knowledge scores and domains of knowledge. Conclusion: The study points out significant gaps in knowledge about forensic sexual assault examination among nurses and nursing students. Improving forensic nursing education through better curriculum integration and in-service education and training is important to prepare nurses for enhancing the survivorcentered care and ensuring proper evidence management.